"I am Malawian, Multicultural or British": Remote acculturation and identity formation among urban adolescents in Malawi. Issue 2 (24th April 2017) - Ferguson, Kim T.; Ferguson, Yuna L.; Ferguson, Gail M.
Abstract : We aimed to better understand multidimensional remote acculturation to South African, United States of America (US), and United Kingdom (UK) cultures among 144 thirteen- to seventeen-year-old ( M = 15 0.28, SD = 1.06; 43.1% female; 36.6% Black African, 23.9% Southeast Asian, 21.8% Multiracial, 16.2% White, 1.4% Other) urban adolescents in Malawi. Adolescents completed questionnaires measuring remote acculturation, cultural exposure, parent-adolescent relationships, and adolescent well-being. A hierarchical cluster analysis identified three remote acculturation clusters: Traditional Malawians (TMs), Westernised Multicultural Malawians (WMMs), and British Assimilated Malawians (BAMs). Clusters differed in their racial and ethnic makeup. BAMs had the lowest cultural exposure to Malawian food, media, communication, and transnationalism. WMMs had higher positive affect than BAMs; WMMs and BAMs reported higher parental autonomy support than TMs; and TMs reported the highest conflict with their mothers. Our findings highlight the significant positive role of remote acculturation in the identity formation and well-being of 21 st century sub-Saharan African adolescents.